Pengaruh Penambahan Minyak Jagung pada Pembuatan Keju Olahan (Sliced Cheese) dengan koagulan Getah Pepaya Kering Terhadap Jumlah Total Yeast, Bakteri, dan Kapang - Lathifa, Aghisna Dwi; Putranto, Wendry Setiyadi; Wulandari, Eka (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Processed cheese is a cheese product made from one or more types of fresh cheese that undergoes further processing to extend shelf life and develop new cheese varieties. Corn oil contains saturated fatty acids, unsaturated fatty acids, and phenolic compounds that can inhibit microbial growth. This study aims to determine the effect of corn oil addition in making sliced cheese with dried papaya latex coagulant on the total of yeast, bacteria, and mold. This study was conducted experimentally using a Completely Randomized Design (CRD), consisting of 4 treatments of corn oil concentration (P0 = 0%, P1 = 5%, P2 = 10%, and P3 = 15%), where each treatment was repeated as many as 5 replicates. Data on the total of yeast, bacteria, and mold were analyzed using the variance test and Duncan's further test. The results showed that the addition of corn oil at 15% in the manufacture of processed cheese (sliced cheese) had a significantly lower effect on the total yeast count of 0.59×103 cfu/g and no significant effect on the total bacteria and mold.